Extension Interventions for Enlightening Tribal Farmers for Enhancing Cotton Production in Nalgonda District, Telangana - Shankar, M.; Khan, M. A. Aariff; Naaiik, R. V. T. Balazzii; Sumalini, K. (International Journal of Bio-resource and Stress Management, 2022)
Cluster Frontline Demonstrations using IPM technologies were conducted on farmer fields’ during two consecutive years of both kharif (June-November 2017 and 2018) by Krishi Vigyan Kendra, Kampasagar, Telangana State, India. The results revealed that, 16.9% increased cotton yield was observed in demonstration plot (2234.0 kg ha-1) against farmers practice (1910.5 kg ha-1). The average gross returns, net returns, and benefit-cost ratios were higher in the demonstration plot as compared to the farmers’ practice. The average cost reduction was (Rs. 41402.0 ha-1) in the demonstration plot when compared to farmers’ practice (Rs. 46190.0 ha-1). Incidence of sucking pests and pink bollworm was low in demonstrations plots and adoption of IPM practices i.e. stem application in cotton at 30 and 45 days after sowing with Monocrotophos and water (1:4) ratio and 60 days after sowing with Imidacloprid and water (1:20) ratio minimize the sucking pests. Further erection of pheromone traps @10 ha-1 at 45 DAS to monitor pink bollworm population and spraying of need-based plant protection chemicals i.e. Azadirachtin 0.15% EC @ 2.5 l ha-1 and Thiodicarb 75% WP @ 1.5 g l-1 at early stages and Emamectin benzoate 5% SG @ 0.5 g l-1 at later stages effectively controlled pink bollworm. The average extension gap, technology gap, and technology index were 323.25 kg ha-1, 266.25 kg ha-1 and 10.65%, respectively. Hence, adoption of IPM technologies play a major role for controlling the pest complex and need arises to adopt and popularize this technology in the cotton farming to mitigate the wider extension gap between improved and farmers’ practices.